Thandarum hernandezi, a new genus and new species of sea cucumber family Sclerodactylidae (Echinodermata: Holothuroidea: Dendrochirotida) from the Southwestern Atlantic Ocean - Martinez, Mariano I.; Brogger, Martín I. (Zootaxa, 2012)
A new genus and a new species of dendrochirotid, Thandarum hernandezi gen. et sp. nov., is described from Buenos Airescoast in the Southwestern Atlantic. For this species is quite significant the body U shape, up to 14.08 mm (along thetrivium), with double row of podia restricted to the ambulacra. Other features are ossicles from body wall with buttonsand 4 pillar tables, tube feet with rods and end plate star-shaped; the introvert with rosettes and tentacles with rods. Thesecharacteristics require the recognition of a new genus, and the new species and represents the first sclerodactylid reported in Argentinean waters.